Analisis Kesadaran Berkelanjutan dalam Pembelajaran Materi Ekosistem di Kelas X SMA Negeri 1 Alalak Banjarmasin - Norliani Norliani; Zevira Fransisca Aurora; Aisya Nabila Savitri (Wahana-Bio: Jurnal Biologi dan Pembelajarannya, 2026)
The problem of increasing waste volume and low awareness of waste management shows a gap between expectations and reality, especially among students. This study aims to analyze the level of sustainability awareness of students at Alalak 1 Public High School in ecosystem learning in terms of knowledge, awareness, attitude, and participation. This quantitative descriptive study involved 52 tenth-grade students through knowledge tests and questionnaires. Based on the diagram, the highest level of ecosystem literacy among students was in the structural category (56%), followed by multidimensional (36%), functional (8%). The results of the analysis show that the level of sustainable awareness is in the high category with an average of 82.26%. Students have a good understanding, positive attitudes, and active involvement in environmental management, although the consistency of concrete actions still needs to be strengthened. This study emphasizes the importance of integrating sustainability values into biology learning to shape a generation with ecological awareness and responsibility towards the environment.